Associations of alcohol consumption status with activities of daily living among older adults in China. Issue 3 (2nd August 2021) - Lee, Yen-Han; Lu, Peiyi; Chang, Yen-Chang; Shelley, Mack; Lee, Yi-Ting; Liu, Ching-Ti
Abstract: Background: With the rapid growth of the elderly population and public health challenges in China, concerns arise related to disability associated with activities of daily living (ADLs) and alcohol consumption status. This study assesses the relationships of alcohol consumption status with basic daily activities among Chinese older adults. Methods: A total of 5, 133 participants aged 60 years or above from three waves of the Chinese Longitudinal Healthy Longevity Survey (2009, 2012, and 2014) were analyzed. Independent ADL items included bathing, dressing, toileting, indoor moving, continence, and feeding (without others' assistance). Multilevel ordered logistic regression model estimation was used to examine the results of total scores based on the Katz index. Multilevel logistic regression models also were estimated to study each index item separately to examine differences across each of the six ADLs. Additional confirmatory factor analysis (CFA) was performed to examine the validity of the index. Results: Preliminary CFA showed that most items had good factor loadings (>0.700), except for continence (0.256) and feeding (0.481). Based on the ordered regression model, former (AOR = 0.412, 95% CI: 0.294, 0.579, p < 0.001) and non-alcohol consumption (AOR = 0.598, 95% CI: 0.447, 0.800, p < 0.001) were negatively associated with the total score. Non-alcohol consumption status was negatively associated with ADL items separately (all p s < 0.05), with the exceptions of continence and feeding. Conclusion: Alcohol consumption may be associated with Chinese older adults' better ADLs. However, further clinical or experimental trials are needed to examine the impact of alcohol consumption on older adults' ADLs.